Transmission of ‘Candidatus Liberibacter solanacearum’ by Bactericera trigonica Hodkinson to vegetable hosts - Teresani, Gabriela; Hernández-Suárez, Estrella; Bertolini, Edson; Siverio, Felipe; Moreno, Aránzazu; Fereres, Alberto; Cambra, Mariano (INIA, 2020)
The bacterium ‘Candidatus Liberibacter solanacearum’ is a recent plant pathogen of several crops in Solanaceae and Apiaceae and is associated with economically important diseases. The bacterium is a carrot seed borne pathogen that can also be transmitted from potato mother tubers and by psyllid vectors. The psyllid Bactericera trigonica Hodkinson was described carrying CaLso associated with vegetative disorders in carrot and celery crops in Spain and its competence to transmit this phloem-limited bacterium among vegetables is currently being investigated. Here electrical penetration graphs showed that B. trigonica fed in the phloem of carrot and celery and probed the phloem in potato, but not in tomato plants. The bacterium was efficiently transmitted to carrot and celery plants when either single B. trigonica or groups of ten fed on these species. An inoculation access period of 24 hours was sufficient for a single B. trigonica to transmit the bacterium to carrot (67.8%), celery (21.1%) and eventually to potato and tomato (6.0%). Higher transmission rates were obtained with 10 individuals on celery (100%), carrot (80%), potato (10%) and tomato (10%). Bactericera trigonica laid eggs, and the hatched nymphs develop into adult on carrot and celery, but not on potato and tomato. CaLso was detected in 20% of the eggs laid by females carrying the bacterium. The results confirmed that B. trigonica is a vector of the bacterium to carrot and celery, and it is discussed the potential role of this psyllid in the transmission of the pathogen to potato and tomato plants.